2017
DOI: 10.1089/vbz.2016.2062
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Middle East Respiratory Coronavirus in Young Dromedary Camels in Jordan

Abstract: Prevalence of Middle East respiratory syndrome coronavirus (MERS-CoV) was determined in 45 dromedary camels from two geographically separated herds in Jordan. Virus shedding was only detected in swabs obtained from the respiratory tract and primarily observed in camels younger than 3 years. MERS-CoV seroprevalence increased with age of camels. Bovine and sheep sera were seronegative. Phylogenetic analysis of partial S2 clustered the Jordanian MERS-CoV strains with contemporary MERS-CoV strains associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 11 publications
0
58
1
Order By: Relevance
“…Sera were analyzed by SARS-CoV-2 spike protein (S) enzyme-linked immunosorbent assay (ELISA) as done previously for MERS-CoV 34 . Briefly, maxisorp (Nunc) plates were coated overnight with 100 ng/well S protein diluted in PBS 35 (a kind gift of Barney Graham, Vaccine Research Center, NIH) and blocked with blocker casein in PBS (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Sera were analyzed by SARS-CoV-2 spike protein (S) enzyme-linked immunosorbent assay (ELISA) as done previously for MERS-CoV 34 . Briefly, maxisorp (Nunc) plates were coated overnight with 100 ng/well S protein diluted in PBS 35 (a kind gift of Barney Graham, Vaccine Research Center, NIH) and blocked with blocker casein in PBS (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…The calves then produced MERS-CoV antibodies by 11-12 months of age (34). In seroprevalence studies, camels <2 years of age demonstrated lower seroprevalence than camels >2 years of age (25,35). Across many countries, the seroprevalence of adult camels is >90% (16,17).…”
Section: Camel-to-camel Transmission Dynamicsmentioning
confidence: 99%
“…MERS-CoV has spread to 27 countries and infected more than 1900 humans with a mortality rate of 40% [2]. Dromedary camels, especially juveniles, contract the infection and shed the virus, without notable symptoms of disease; this is now known to have been occurring since the early 1980s [8][9][10][11][12][13]. The mechanism of camel to human transmission is still not clear, but several primary cases have been associated with camel contact, which is considered an important risk factor [14][15][16].…”
Section: Introductionmentioning
confidence: 99%